Vitamin D status in mothers with pre-eclampsia and their infants: a case–control study from Serbia, a country without a vitamin D fortification policy. Issue 10 (18th April 2016) - Djekic-Ivankovic, Marija; Weiler, Hope; Jones, Glenville; Kaufmann, Martin; Kaludjerovic, Jovana; Aleksic-Velickovic, Vesna; Mandić, Ljuba M; Glibetic, Maria
Abstract: Objective: The objective of the present study was to determine if vitamin D intake and status are associated with pre-eclampsia in a country without a vitamin D fortification policy. Design: A case–control study of pregnancies with (case) and without (control) pre-eclampsia was conducted from January to April when UVB is minimal. Maternal and cord blood obtained at delivery were measured for plasma 25-hydroxycholecalciferol (25-OH-D3 ), 3-epimer of 25-OH-D3 (3-epi-25-OH-D3 ) and 24, 25-dihydroxycholecalciferol (24, 25-(OH)2 D3 ) by LC–MS/MS and maternal 1, 25-dihydroxyvitamin D (1, 25-(OH)2 D). Differences between groups were tested with ANOVA and Bonferroni post hoc tests ( P <0·05). Setting: Clinical Center of Serbia. Subjects: Pregnant women with and without pre-eclampsia ( n 60) and their infants. Results: Exogenous vitamin D intake (0·95–16·25 µg/d (38–650 IU/d)) was not significantly different between groups. Women with pre-eclampsia delivered infants at an earlier gestational age and had significantly lower mean total plasma 25-hydroxyvitamin D (25-OH-D; case: 11·2 (sd 5·1); control: 16·1 (sd 5·7) ng/ml; P =0·0006), 25-OH-D3 (case: 10·0 (sd 4·9); control: 14·2 (sd 5·8) ng/ml; P =0·002), 3-epi-25-OH-D3 (case: 0·5 (sd 0·2); control: 0·7 (sd 0·2) ng/ml; P =0·0007) and 1, 25-(OH)2 D (case: 56·5 (sd 26·6); control: 81·0 (sd 25·7) pg/ml; P =0·018), while 24, 25-(OH)2 D3 was not different between groups. Infants did not differ in total plasma 25-OH-D, 25-OH-D3, 3-epi-25-OH-D3 and 24, 25-(OH)2 D3, but the mean proportion of 3-epi-25-OH-D3 was higher in the infant case group (case: 7·9 (sd 1·1); control: 7·0 (sd 1·4) % of total 25-OH-D3 ; P =0·005). Conclusions: A high prevalence of vitamin D deficiency, as defined by plasma 25-OH-D<12 ng/ml, was observed in 47 % of all mothers and 77 % of all infants. These data underscore the need for prenatal vitamin D supplementation and a food fortification policy in Serbia.